EFFECT OF SAPONIN-PODS EXTRACT ACACIA (ACACIA MANGIUM) TO HEMATOCRIT, HEMOGLOBIN AT TILAPIA (OREOCHROMIS NILOTICUS) - Is Yuniar; Win Darmanto; Agoes Soegianto (UPT Penerbitan Universitas Jember, 2016)
Problem of aquaculture shrimp, one of which is wild fish, competitor. Usually to eliminate the use of saponin from tea seed. saponin to kill fish competitors, (tilapia) are entered when filling water. Saponin to kill fish competitors, (tilapia) are entered when filling water. Saponin used from tea seed meal is imported. Indonesia is rich in biological resources of plants / substances that secondary metabolites naturally untapped optimal. The study was conducted in a laboratory scale with a completely randomized factorial design, using a series of six concentrations and three replicates for each species. LC50 analysis using probit analysis. Unfortunately, there was no scientific information for it. It has been done a laboratory work to study chemical compounds of pod Acacia (Acacia mangium) by phytochemical screening and measure those quantitatively. The result of these were that pod Acacia (Acacia mangium) contain alkaloid, flavonoid, tanin, saponin, steroid, and terpenoid. The results of this study indicate LC50-96h values for Pod Acacia mangium at salinity 0, 5, 10 and 15 promil is 5.487 ppm, 4.313 ppm, 3.985 ppm and 2.944. Value hemoglobin at 0promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 11.353±0.63)g/dL,10.607±0.18g/dL, 9.860±0.36 g/dL and 8.80±0.60. Value hemoglobin at 5promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 8.86±1.02 g/dL,7.76±0.943 g/dL, 7.42±0.71 g/dL and 4.68±0.53g/dL. Value hemoglobin at 10 promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 7.34±1.95 g/dL,6.07±0.755 g/dL, 5.23±1.34 g/dL and 3.23±035 g/dL. Value hemoglobin at 15promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 8.570±0.478 g/dL,5.18±0.876 g/dL, 3.42±0386 g/dL and 3.817±0.355g/dL. Value hematocrit at 0promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 35.033±3.32g/dL, 31.2±0.90 g/dL, 29.367±0.97 g/dL and26.60±1.345. Value hematocrit at 5promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 25.633±1.24 g/dL, 23.90±2.68 g/dL, 18.367±2.554 g/dL and 12.867±2.38 g/dL. Value hematocrit at 10 promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 21.567±6.134 g/dL,18.567±1.48 g/dL,14.767±3.46 g/dL and 10.53±3.38 g/dL. Value hematocrit at 15promil at conentration saponin-pod Acacia 0ppm, 5ppm, 10ppm dan 15ppm consecutive is 26.100±1.42 g/dL, 15.667±2.79 g/dL,9.933± 2.04 g/dL and 11.933±1.19 g/dL. Saponin of acacia may lower hematocrit and hemoglobin an indication of damage to the red blood cells occurs hemolysis.